2012
DOI: 10.1086/667894
|View full text |Cite
|
Sign up to set email alerts
|

Ant Societies Buffer Individual-Level Effects of Parasite Infections

Abstract: Parasites decrease host fitness and can induce changes in host behavior, morphology, and physiology. When parasites exploit social insects, they influence not only infected individuals but also the society as a whole. Workers of the ant Temnothorax nylanderi are an intermediate host for the cestode Anomotaenia brevis. We studied a heavily parasitized population and found that, although parasite infection had strong and diverse consequences for individual workers, colony fitness remained unchanged. At the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 51 publications
(69 reference statements)
3
74
5
Order By: Relevance
“…First, the reduced flight response of infected T. nylanderi workers in response to nest attacks would presumably increase the tapeworms' transmission into the definitive avian host, which preys upon ant brood or beetle larvae. Causes of the lower escape rate might be, in addition to the lower activity of infected workers [26], their smaller eye and body size, and shorter legs [25]. Second, the higher survival of infected ants would extend the parasite's time period for transmission, because predation events by woodpeckers might be rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the reduced flight response of infected T. nylanderi workers in response to nest attacks would presumably increase the tapeworms' transmission into the definitive avian host, which preys upon ant brood or beetle larvae. Causes of the lower escape rate might be, in addition to the lower activity of infected workers [26], their smaller eye and body size, and shorter legs [25]. Second, the higher survival of infected ants would extend the parasite's time period for transmission, because predation events by woodpeckers might be rare.…”
Section: Discussionmentioning
confidence: 99%
“…It is puzzling, as workers-both from parasitized and unparasitized colonies-were more aggressive towards infected ants, be it non-nest-mates or nest-mates [26]. This suggests that workers discriminated infected from uninfected ants due to the quantitative changes in their chemical profile [25], although aggression did not further increase with parasite load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group size may improve social mechanisms of infection control. Temnothorax nylanderi colonies infected with a cestode parasite were larger than uninfected colonies; worker productivity did not differ with infection state, suggesting that larger colonies may buffer parasitism (Scharf et al 2012). In Acromyrmex echinatior , workers experimentally infected with the fungus Metarhizium had significantly lower survival in isolation than when maintained with nestmates (Hughes et al 2002).…”
Section: Worker Longevity and Colony Fitnessmentioning
confidence: 99%
“…When inhabiting poorer nest sites, Temnothorax ants produce a male‐biased sex ratio (Strätz & Heinze, ). It was also shown that the presence of parasites influences the sex ratio, and parasitised colonies produce a male‐biased sex ratio (Scharf et al ., ). In the present study, colonies more frequently inhabited nests located outside balsam patches, but, unexpectedly, when living inside patches of alien balsam, they produced a more female‐ – not male‐ – biased sex ratio.…”
Section: Discussionmentioning
confidence: 97%